Making sense of multilevel governance and governance coordination in Brazil: The case of the Bolsa Verde Programme - Kull, Michael; Pyysiäinen, Jarkko; Christo, Giovanna; Christopoulos, Stamatios (Taylor & Francis, 2017)
Brazil is an example of a challenging governance context par excellence: continental size, multi-levelled governance structures and diverse administrative cultures meet with ambitious, large-scale policy needs and objectives. The multilevel governance approach is applied here to analyse implementation and governance coordination of the Bolsa Verde Programme (BVP). Through a close reading of the narratives told by three programme officials – and zooming in on jointly exercised governance functions known from the metagovernance approach – we analysed how BVP’s programmatic governance coordination was made sense of. The analysis showed that our interviewees were well aware of the shortcomings of the governance coordination in BVP, understood as rather hierarchical, centrally driven and often tackling challenges of vertical multi-actor coordination in a reactive ad-hoc manner. However, since the implementers have been able to creatively and skilfully solve governance coordination challenges, possibilities for developing more systematic and inclusive (meta)governance approaches seem feasible.
Keywords: multilevel governance; governance coordination; metagovernance; Bolsa Verde Programme; narrative ananlysis; Brasilia; governance